2008
DOI: 10.1089/thy.2007.0222
|View full text |Cite
|
Sign up to set email alerts
|

Altered Intestinal Absorption of L-Thyroxine Caused by Coffee

Abstract: Coffee should be added to the list of interferers of T4 intestinal absorption, and T4 to the list of compounds whose absorption is affected by coffee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
105
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(113 citation statements)
references
References 13 publications
2
105
0
6
Order By: Relevance
“…Therefore, it is recommended to obey a 30-minute interval between thyroxine pill ingestion and breakfast. A series of reports have demonstrated that coffee, especially espresso coffee, impairs thyroxine absorption (50). Dietary fibers appear to have a smaller, but still significant effect on thyroxine absorption (51).…”
Section: Nutritional Habitsmentioning
confidence: 99%
“…Therefore, it is recommended to obey a 30-minute interval between thyroxine pill ingestion and breakfast. A series of reports have demonstrated that coffee, especially espresso coffee, impairs thyroxine absorption (50). Dietary fibers appear to have a smaller, but still significant effect on thyroxine absorption (51).…”
Section: Nutritional Habitsmentioning
confidence: 99%
“…Due to this, L-T 4 is usually taken with water in the morning before breakfast (3). Taking L-T 4 with coffee, or with water followed by coffee within a few minutes, results, in fact, in poor TSH response in many patients (4). Traditionally, T 4 is available in tablet form worldwide, but novel formulations in soft gel capsule or liquid form are available now.…”
Section: Introductionmentioning
confidence: 99%
“…One such factor is the amount of LT 4 absorbed in the gastrointestinal tract, which is altered by various medical disorders (10)(11)(12), several medications (13)(14)(15)(16), and food and drink (17)(18)(19). The timing of LT 4 administration also has an impact on its absorption (18,(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%